EFEKTIFITAS PENGGUNAAN INTERACTIVE EDUCATIONAL MULTIMEDIA LEARNING BERBASIS TEORI KOGNITIF TERHADAP DYSLEXIC STUDENT DI SEKOLAH DASAR - Sinaga, Reflina; Tanjung, Darinda Sofia (JGK (Jurnal Guru Kita), 2019)
Abstract: Effectiveness of the Use of Interactive Interactive Multimedia Learning Based on Cognitive Theory of Dyslexia Students in Primary Schools. This type of research is research and development with quantitative and qualitative descriptive methods. The research aims to analyze the development of interactive educational multimedia learning in terms of cognitive theory in dyslexic students in elementary schools in Medan Denai district. Analysis of the data in this research will be distinguished above, interactive data validation data analysis through two stages namely descriptive qualitative and quantitative analysis. The percentage of display aspects given by the validator is 89.60%. For operational aspects, the percentage score data is 95.33% and the validator interaction aspect gives a percentage score of 93.53%. Based on these data, the learning media developed can be categorized as very good and feasible to be used as supporting analysis.Keywords: Multimedia learning, cognitive theory, dyslexic studentAbstrak: Efektifitas Penggunaan Interactive Educational Multimedia Learning Berbasis Teori Kognitif Terhadap Dyslexic Student di Sekolah Dasar. Jenis penelitian ini adalah penelitian pengembangan (Research and Development) dengan metode deskriptif kuantitaif dan kualitatif. Pelaksanaan penelitian bertujuan untuk menganalisis pengembangan interactive educational multimedia learning ditinjau dari teori kognitif pada dyslexic student di sekolah dasar kecamatan Medan Denai. Analisis data dalam penelitan ini akan dibedakan atas, analisis data validasi media interaktif melalui dua tahap yakni analisis deskriptif kualitatif dan kuantitatif.skor persentase aspek tampilan yang diberikan validator adalah 89,60%. Untuk aspek operasional didapat data skor persentase 95,33% dan aspek interaksi validator memberikan skor persentase sebesar 93,53%. Berdasarkan data tersebut maka media pembelajaran yang dikembangkan dapat dikategorikan sangat baik dan layak untuk digunakan sebagai pendukung analisis.Kata Kunci: Multimedia learning, teori kognitif, dyslexic student